The Effect of Rice Varieties on Silica Purification from Rice Husk Ash as Adsorbent for Mn(II) - Mersiana Bria Mosa; Hermania Em Wogo; Dodi Darmakusuma (Jurnal Sains dan Terapan Kimia, 2023)
The influence of rice types on the purification of rice husk ash was investigated by extracting silica and purifying it with a 12% NaOH solution, followed by the coprecipitation technique. Rice husk samples were from Mbay (Nagekeo Regency) with two different varieties, Ciherang and Inpari 42, and from Soa (Ngada Regency) with Ciherang variety. The silica produced in this research was characterized using UV Vis spectrophotometry to obtain the surface area value. The surface acidity value was calculated using the acid-base titration method. Using XRF, the purity of silica was determined. Ciherang Mbay, Ciherang Soa, and Inpari Mbay had surface area values of 18.397 m2/gram, 18.347 m2/gram, and 18.491 m2/gram, respectively. The surface acidity value of the three samples was 45.1 mmol/gram, 45.5 mmol/gram, and 44.7 mmol/gram, respectively. The purity of silica from rice husk ash Ciherang Mbay, Ciherang Soa, and Inpari Mbay samples based on XRF was 98.6%, 98.3%, dan 99.2%, respectively. Silica with the highest purity (Inpari Mbay variety) was applied as an adsorbent in the adsorption process of manganese (Mn(II)) metal ion with an adsorption capacity of 212.76 µmol/gram and adsorption energy of 38.165 kJ/mol through chemical adsorption. Keywords: purification, rice varieties, silica, adsorption, manganese